Microbiological and Chemical Safety of Street-Vended Foods in Urban Markets - Oluwakemisola, Daramola Precious (Darul Yasin Al Sys, 2025)
Street-vended foods are an essential component of urban diets and local economies in Nigeria; however, concerns over their microbiological and chemical safety remain prevalent. This cross-sectional study evaluated contamination levels in 120 food samples collected from three distinct vending environments in Benin City, Edo State: a central wholesale market, a neighborhood produce market, and a roadside trading cluster. Microbiological analysis focused on total viable counts (TVC), Escherichia coli, coliforms, Salmonella spp., Staphylococcus aureus, and Bacillus cereus, while chemical assessments quantified lead (Pb), cadmium (Cd), mercury (Hg), and selected pesticide residues using Atomic Absorption Spectrophotometry (AAS) and Gas Chromatography–Mass Spectrometry (GC–MS). Results revealed that 38% of samples exceeded the Codex Alimentarius TVC threshold of 5 log₁₀ cfu/g. E. coli was present in 25% of samples, with the highest incidence in fresh salads (45%), while Salmonella spp. appeared in 8%, predominantly in meat and salad items. S. aureus was detected in 30% of samples, especially in fried snacks and grilled meats. Pb levels exceeded permissible limits in 15% of samples, particularly grilled meats and roadside salads; however, Cd and pesticide residues generally remained within Codex maximum residue limits. Identified contamination sources included environmental exposure, inadequate food handling, and the use of unsafe water. These findings highlight the need for strengthened hygiene training for vendors, regulatory oversight, and infrastructural improvements to reduce health risks while sustaining livelihoods. Ensuring food safety in the street food sector is vital for public health protection in rapidly urbanizing contexts.